2006
DOI: 10.1002/app.23409
|View full text |Cite
|
Sign up to set email alerts
|

Modification of polyolefin films surface with sodium hypochlorite

Abstract: Surface modification of high-density-polyethylene (HDPE) and linear-low-density polyethylene (LL-DPE) films is promoted by sodium hypochlorite solutions using two different processes (I and II). Such an oxidation system introduces limited amounts of carbonyl-carboxyl and hydroxyl groups onto the surface of hydrocarbon polymers. FTIR, XPS, and SEM were used to assess the efficiency of the oxidation. The hydrophilicity of the studied surfaces was investigated by the sessile drop technique and the Wilhelmy plate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…ATR‐FTIR and XPS, two commonly used characterization methods for surface functional groups, have been used to identify carboxyl end groups and ester units on polymer surfaces 34, 36, 43. However, neither provided sufficient signal to differentiate the carboxyl end groups from the ester units abundant on PLLA fiber surfaces in our study (results were not shown here).…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…ATR‐FTIR and XPS, two commonly used characterization methods for surface functional groups, have been used to identify carboxyl end groups and ester units on polymer surfaces 34, 36, 43. However, neither provided sufficient signal to differentiate the carboxyl end groups from the ester units abundant on PLLA fiber surfaces in our study (results were not shown here).…”
Section: Discussionmentioning
confidence: 62%
“…Similarly, when NaOCl solution is used, the etching process starts with nucleophilic attack of the OH − on the carbonyl carbon on the fiber surfaces. However, the newly generated hydroxyl end groups can be further oxidized into carboxylate end groups, owing to the presence of abundant hypochlorite (OCl − ) groups in the NaOCl solution 32–35, 40, 41. In the latter case, more carboxyl groups are generated on the PLLA surfaces and some of them are as shown for (III), which are connected to carbonyl of the ester instead of the carbon alpha to the ester.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations